2008
DOI: 10.3923/pjbs.2008.480.483
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance, Carcass Characteristics and Haematological Parameters of Broiler Chicks Reared in Cage and Floor

Abstract: This study was conducted to determine the effect of housing systems on the performance, carcass characteristics and the haematology of 150 four-week old Anak titan strains of broiler chicks in a completely randomized design. The birds were allocated randomly into two treatment (cage and floor) groups of three replications containing 25 birds per replicate. They were maintained for a period of 4 weeks and data were collected on; final body weight, weight gain, feed intake, feed:gain and mortality. At the 56th w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
4
11
1
Order By: Relevance
“…In general, the results indicate that the studied hematological blood profile of the present experiment were not adversely affected by the housing systems (Mench 1992), and depicted equally sound health status and no infection among the experimental birds as a result of the housing system. This finding are confirmed by Sogunle et al (2008) found that no significant difference observed in the hematological parameters of broiler chickens due to housing system. However, rearing area significantly affected WBCs, RBCs and Hb, while insignificant differences detected for hetrophils, lymphocyte and H/L ratio, although, the values obtained were within the range reported by Sogunle et al (2006).…”
Section: Discussion Productive Performance Live Body Weight (Lbw) Andsupporting
confidence: 71%
“…In general, the results indicate that the studied hematological blood profile of the present experiment were not adversely affected by the housing systems (Mench 1992), and depicted equally sound health status and no infection among the experimental birds as a result of the housing system. This finding are confirmed by Sogunle et al (2008) found that no significant difference observed in the hematological parameters of broiler chickens due to housing system. However, rearing area significantly affected WBCs, RBCs and Hb, while insignificant differences detected for hetrophils, lymphocyte and H/L ratio, although, the values obtained were within the range reported by Sogunle et al (2006).…”
Section: Discussion Productive Performance Live Body Weight (Lbw) Andsupporting
confidence: 71%
“…In another study [33] , performance and carcass quality of broiler chickens grown under chronic stress were found to be significantly impaired since the increase in synthesis of corticosterone impairing protein synthesis. Sogunle et al [7] referred that dressing percentage and breast weight were higher in the floor housing than cage housing while Bahreiny et al [29] and Lacin et al [9] did not find any difference between groups in carcass yield and parts. Antioxidant metabolism was found to be similar in terms of both groups.…”
mentioning
confidence: 99%
“…From now on, reduced labor costs per square meter, increased uniformity, improved feed efficiency, more production per unit area, unnecessity of the use of litter, disappearance of dust and wet litter problems which are the major problems in floor system, minimum incidence of diseases such as enteritis and coccidiosis because of decreasing contact with manure, increase at annual production because of convenience of disinfection and cleaning operations, easy and stressfree transport to slaughterhouse have been detected as the advantages of use of cages for broiler breeding [4][5][6] . However, high initial investment cost, difficulty at poultry management and control of environmental factors at largescale flocks, deteriorating welfare, increased mortality rates related to leg and wing disorders of chickens, softening of bones, leg and wing fractures, perozis, defects of brisket and decline in quality of meat have been obtained as the disadvantages [3,[7][8][9][10] .Although cages have been banned in broilers and layers in EU, with more intensive production in a small land, the cage production seems quite attractive and has been quickly growing over the World, especially in Russia, the Middle East, several Asian countries, Africa and Eastern European countries in recent years [10] . However, there is the lack of information in cage reared broilers, especially in commercial flocks.…”
mentioning
confidence: 99%
“…The later authors added that chickens reared on floor had high (P≤0.05) percentages of gizzard than those raised in cages. As well as, Sogunle et al (2008) concluded that the floor system revealed higher (P≤0.05) values in the dressing percentage than the battery cages one.…”
Section: Carcass Characteristicsmentioning
confidence: 84%
“…Many researches conducted on productivity of broiler chickens in battery cages showed different results. Some studies cleared that floor reared broilers have significantly higher growth rates and heavier final body weights as compared to cage reared groups (Tolon and Yalcin, 1997 ;Fouad et al, 2008), while other authors found no significant difference in weight gain (Sogunle et al, 2008 ;Swain et al, 2002).…”
Section: Animal and Poultry Productionmentioning
confidence: 99%